2017
DOI: 10.1177/0748730417693480
|View full text |Cite
|
Sign up to set email alerts
|

Acute Effects of Morning Light on Plasma Glucose and Triglycerides in Healthy Men and Men with Type 2 Diabetes

Abstract: Ambient light intensity is signaled directly to hypothalamic areas that regulate energy metabolism. Observational studies have shown associations between ambient light intensity and plasma glucose and lipid levels, but human data on the acute metabolic effects of light are scarce. Since light is the main signal indicating the onset of the diurnal phase of physical activity and food intake in humans, we hypothesized that bright light would affect glucose and lipid metabolism. Therefore, we determined the acute … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
26
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 53 publications
8
26
1
1
Order By: Relevance
“…After nocturnal exposure to blue light, increased glucose levels were observed in male Arvicanthis regardless of the type of diet, together with decreased plasma insulin levels. These results further stress the negative effects of nocturnal light on glucose tolerance, putatively by inhibiting insulin release, as previously also described in rats (Opperhuizen et al ) and in healthy and T2D adults (Cheung et al ; Versteeg et al ). It has been described before how light during the dark phase via the SCN can increase the sympathetic activity and decrease the parasympathetic activity of autonomic nerves that reach peripheral organs like the liver, the pancreas and the adrenal gland (Niijima et al , ; Ishida et al ); this would lead to an increase in the hepatic gluconeogenesis, glycogenolysis, and a decrease in the release of insulin from the beta cells which can explain our current results in the glucose tolerance test.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…After nocturnal exposure to blue light, increased glucose levels were observed in male Arvicanthis regardless of the type of diet, together with decreased plasma insulin levels. These results further stress the negative effects of nocturnal light on glucose tolerance, putatively by inhibiting insulin release, as previously also described in rats (Opperhuizen et al ) and in healthy and T2D adults (Cheung et al ; Versteeg et al ). It has been described before how light during the dark phase via the SCN can increase the sympathetic activity and decrease the parasympathetic activity of autonomic nerves that reach peripheral organs like the liver, the pancreas and the adrenal gland (Niijima et al , ; Ishida et al ); this would lead to an increase in the hepatic gluconeogenesis, glycogenolysis, and a decrease in the release of insulin from the beta cells which can explain our current results in the glucose tolerance test.…”
Section: Discussionsupporting
confidence: 88%
“…Whether this effect is dependent on the activation of melanopsin in the ipRGCs and thus its projections to different parts of the brain, remains to be investigated. Nevertheless, our present results in this diurnal rodent and previous results in rats (Opperhuizen et al ) and humans (Cheung et al ; Versteeg et al ) are sufficient to raise the awareness about the deleterious effects of light at night, especially short‐wavelength coming from light‐emitting diodes based products, on glucose metabolism and food intake.…”
Section: Discussionsupporting
confidence: 55%
“…Nor did light therapy affect glycemic control. On the basis of recent publications, we may have anticipated glycemic control to deteriorate as a result of the acute effects of light on both preprandial and postprandial glucose concentrations (33)(34)(35)). Yet, 30 min of light daily may not be enough to change HbA 1c .…”
Section: Discussionmentioning
confidence: 99%
“…Individuals on a hypocaloric, three-mealper-day diet lost more weight when the majority of the food was consumed in the morning, as opposed to the evening (51). However, no significant changes in glycemia, insulin sensitivity, or respiratory exchange ratio (RER, defined as the ratio between the amount of carbon dioxide produced and oxygen used during breathing) were observed when obese, insulin-resistant men were exposed to a hypocaloric diet with food provided in the morning (56). In the context of cancer, two studies found that a fasting period of more than 13 hours resulted in lower risk of breast cancer recurrence than that in subjects who fasted less than 13 hours (57,58).…”
Section: Diet and Healthmentioning
confidence: 99%